Acute Insulin Resistance Following Injury - Li, Li (2009)
Hyperglycemia and insulin resistance often occur following injury and/or critical illness. While intensive insulin treatment reduces hyperglycemia, mortality and morbidity in certain patients, little is known regarding the pathophysiology of acute insulin resistance following injury and infection. Studies suggest that acute insulin resistance is complex and may differ in a tissue-specific manner, involving multiple causative factors and intracellular signaling pathways. Therefore, the advantages of intensive insulin therapy may not be uniform to all injuries or critical illnesses. Clearly, the increased incidence of hypoglycemic incidents following intensive insulin therapy indicates a need to understand the underlying molecular mechanisms of the acute development of insulin resistance, which will allow a more targeted approach to treating altered glucose metabolism of critically ill patients.